EFEK PENAMBAHAN SERAT POLYPROPOYLENE TERHADAP DAYA LEKAT DAN KUAT LENTUR PADA REHABILITASI STRUKTUR BETON DENGAN SELF-COMPACTING REPAIR MORTAR (SCRM) - Agus Santoso , Slamet Widodo (Universitas Negeri Yogyakarta, 2010)
ABSTRACTIn the cases of repairing and rehabilitation work of existing concrete structures,interface bond strength between old (substrate layer), and new concrete (overlay) willbe one of the main factors that will significantly affect the quality of the strengthenedstructures. Considering its unique fresh characteristics, self-compacting concrete offersmore advantages in repairing and rehabilitation works. Effects of polypropylene fiberaddition on interface shear bond strength, and the flexural strength of bi-layer concrete(substrate and overlay) were investigated in this experimental study. In this researchworks, polypropylene fibers added at 0 kg/m3, 1 kg/m3, 2 kg/m3, and 3 kg/m3 in thefresh mix of self compacting concrete that will be used as the overlay layer. The freshcharacteristics of self-compacting concrete were investigated using slump-flow test.After 28 days of substrate layer (normal concrete) age, self-compacting concrete thatutilized as overlay layer were casted on the substrate layer. Interface bond strengththat tested using Bi-surface Direct Shear Method, and bi-layer (substrate and overlay)concrete flexural strength were investigated 28 days after the overlay layer casted.Each variant of the bond strength and flexural strength investigated using 3 standardspecimens, therefore totally 36 specimens were tested. Based on the tests results, itcan be concluded several point s as follows; (1) in the case of shear bond strength,polypropylene fiber addition lead the improvement of shear bond strength between newand old concrete. In the dosage of 0 kg/m3, 1 kg/m3, 2 kg/m3 and 3 kg/m3, the resultedshear bond strength were 1,985 MPa, 1,704 MPa, 2,519 Mpa, dan 2,489 MPa, (2)Polypropylene fiber addition also has positive effect on the flexural strength of thestrengthened concrete. Using 0 Kg/m3, 1 kg/m3, 2 kg/m3, and 3 kg/m3 ofpolypropylene fiber addition, the observed flexural strength were 4,156 MPa , 4,988MPa, 2,601 MPa, and 2,543 MPa, and (3) based on the tests results it can besuggested that 1 kg/m3 of polypropylene fiber addition is the optimum composition forthe use of polypropylene fiber reinforced self-compacting concrete as a overlay layerfor repairing, and rehabilitation of concrete structures.Keywords: Polypropylene fiber, Interface Bond Strength, Flexural Strength